Sistemas de informação integrado a smart meter construído com arduino - CAVALHEIRO, Rafael de Souza (2019)
This work presents a study of the techniques used in the development of an Information System with requirements for the design of a Smart Grid, integrated with a Smart Meter prototype built with Arduino, in order to perform an experiment with technologies that enable a Smart Grid based on an application layer, where different modes of communication occur using Information Technology resources. The system consists of manipulating power data (W) collected from a residential power grid, monitoring each household appliance that makes up the consumption of this home network. The data collection is performed by the Smart Meter that transfers the data via computer network and stores it in a database. The purpose of the system is to inform consumption (kWh) and tariff (R$) of energy in real time and present data that assist the user in the decision making on consumption control. The research presents the process of creating a system integrated to a Smart Meter, using techniques of software engineering and theoretical foundation in Information Technologies, conducting an interdisciplinary study in Information Systems as an enabling technology of Smart Grid.